Computational study adsorption of mercaptopurine in generation G3 and G5 PAMAM dendrimers - Ashrafi, Frydon; Mahbobi, Tahereh; Ghasemi, Ashraf Sadat (Ciência e Natura, 2015)
Due to its unique properties of dendrimers as well as with high-level groups, a special ability to carry drugs. In this study compared the interaction between the two generations of poly (amidoamine) PAMAM (G3and G5) dendrimers and the drug 6-mercaptopurine (6-MP) and the drug entrapment within the structure of dendrimers the electrostatic and covalent complexation of drugs to the dendrimer surface have been studied. The use of drug-dendrimer complex enhanced drug solubility and bioavailability of the drug.